Odpowiedź :
Odpowiedź:
a) 4 do potęg 5 × 5 do potęgi 6
[tex]4^{5}[/tex]*[tex]5^{6}[/tex]=[tex]4^{5}[/tex]*[tex]5^{5}[/tex]*5=[tex](4*5)^{5}[/tex]*5=[tex]20^{5}[/tex]*5=[tex](2*10)^{5}[/tex]*5=[tex]2^{5}[/tex]*[tex]10^{5}[/tex]*5=32*100000*5=160*100000=
= 16000000
b) ( 3/5) do potęgi 5 × ( 5/3) do potęgi 6
[tex](\frac{3}{5}) ^{5}[/tex] *[tex](\frac{5}{3} )^{5}[/tex]=[tex](\frac{3}{5} *\frac{5}{3}) ^{5}[/tex]=[tex]1^{5}[/tex]=1
c) (4/9) do potęgi 7÷ (2/9) do potęgi 8
[tex](\frac{4}{9}) ^{7}[/tex]:[tex](\frac{2}{9}) ^{8}[/tex]=[tex](\frac{4}{9}) ^{7}[/tex]*[tex](\frac{9}{2} )^{8}[/tex]=[tex](\frac{4}{9} )^{7}[/tex]*[tex](\frac{9}{2} )^{7}[/tex]*[tex]\frac{9}{2}[/tex]=[tex](\frac{4}{9}*\frac{9}{2} ) ^{7}[/tex]*[tex]\frac{9}{2}[/tex]=[tex]2^{7}[/tex]*[tex]\frac{9}{2}[/tex]=2*[tex]2^{6}[/tex] *[tex]\frac{9}{2}[/tex]=[tex]2^{6}[/tex]*9=64*9=576
d) ( 1 i 4/9) do potęgi 5 ÷ (4 i 1/3) do potęgi 4
[tex](1\frac{4}{9}) ^{5}[/tex]:[tex](4\frac{1}{3}) ^{4}[/tex]=[tex](\frac{13}{9})^{5}[/tex]:[tex](\frac{13}{3}) ^{4}[/tex]=[tex](\frac{13}{9}) ^{5}[/tex]*[tex](\frac{3}{13} )^{4}[/tex]= [tex]\frac{13}{9}[/tex]*[tex](\frac{13}{9}) ^{4}[/tex]*[tex](\frac{3}{13}) ^{4}[/tex]=[tex]\frac{13}{9}[/tex]*[tex](\frac{13*3}{9*13} )^{4}[/tex]=[tex]\frac{13}{9}[/tex]*[tex](\frac{1}{3}) ^{4}[/tex]=[tex]\frac{13}{9}[/tex]*[tex]\frac{1}{3^{2} }[/tex]*[tex]\frac{1}{3^{2} }[/tex]=
=[tex]\frac{13}{9*9*9}[/tex]=[tex]\frac{13}{729}[/tex]=0,018
Szczegółowe wyjaśnienie: